Amanat Tentang Nilai Pendidikan Karakter dalam Novel Selena Karya Tere Liye sebagai Bahan Ajar Sastra di SMA - Anisya, Galih Rismon; Cahyani, Dzikrina Dian; Hapsari, Theresia Ratna Ning (UPA Bahasa Universitas Tidar And HISKI Kedu, 2022)
This study aims to describe the message about the value of character education in Tere Liye's novel Selena and produce the implementation of the message about the value of character education in Tere Liye's novel Selena as a literature teaching material in high school. The approach in this study is a descriptive qualitative approach. The research subject is the message about the value of character education in the novel Selena. The data are in the form of sentences and paragraphs containing a message about the value of character education in the novel Selena. The data source of this research is the novel Selena by Tere Liye. Data collection techniques used reading and note-taking techniques. Then the data analysis technique uses content analysis techniques. The results of the study found four values ​​of character education, namely, religious values, integrity, mutual cooperation, and independence. Implementation of research results in the form of handouts for learning literature for class XII SMA Curriculum 2013. Contains material KD 3.9 analyzing the content and language of novels and KD 4.9 designing novels by paying attention to content and language.